Effects of in-season strength training on physical fitness and injury prevention in north african elite young female soccer players - Darragi, M.; Zouhal, H.; Bousselmi, M.; Karamti, H. M.; Clark, C. C. T.; Laher, I.; Hackney, A. C.; Granacher, U.; Zouita, A. B. M. (Sports Medicine - Open, 2024)
Background Strength training (ST) primarily enhances physical fitness (e.g., muscle strength, power, speed) and bone density in female soccer players. Less information is available on the injury preventive effects of ST in female athletes. Accordingly, this study aimed to investigate the effects of a 12-week in-season ST on measures of physical fitness and injury occurrence in young elite female soccer players.